(3Sja GdfWb aj Yde GdefWbs - (3GdBeOj, GdbjGS (B- (3GdTQjaj, eMeO Hf YHO Gddg (B, (3cGf MjG (B1175 (3g`s
(3ChdgG (B:s
(3cja dG fMeO def ejR HaUhd CLfGS GdecGQe fhY GdEfSGf hbO cGf GdWdGH eTJZdjf HbQGAI QSGdI GdCHgQj YfOeG CdaJ dJdc TQMG djHjf ehGba eSGFdgG Yf ebGUOgG hjejR OdGFd eWGdYgG Yf RhGFOgG s
(3BNQgG (B:s
(3aGdeUfa CTGQ Edi GdMbjbI hde jPcQ ZjQg dXghQ GdebGjSI abGd aGSJKfGA Yjf CMO GdLRFjf jfJL fbjV GdBNQ hfbjV GMOgeG jfJL Yjf GdBNQ deG YQaJ BfaG aJOHQ aJM Gddg Ydjc JeJs
(3JHUQI GdYfhGf (B:s
(3TQM EjSGZhLj ddCHgQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3/431s
(3gOjI GdYGQajf(B1/369s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs